WANPRESTASI TERHADAP AKTA PENGAKUAN UTANG DIBAWAH TANGAN DENGAN JAMINAN SERTIFIKAT HAK MILIK ATAS TANAH DITINJAU DARI PASAL 12 UNDANG-UNDANG NOMOR 4 TAHUN 1996 TENTANG HAK TANGGUNGAN ( Analisis Putusan Kasasi Nomor 837 K/Pdt/2019 ) - Aria Dimas Harapan; Andi Safira Yan Istiany (Program Studi Hukum Universitas Pamulang, 2020)
Starting from the need for capital, in practice some people are reluctant to make credit with banks, because the process is considered difficult, and too convoluted. Therefore, some people prefer to borrow a certain amount of money from individuals or what is better known as debt or credit. Talking about the debt and credit agreement, it will be closely related to collateral because every creditor needs a sense of security for the funds he lends. The author's research is made to examine and find out what efforts can be made if there is default in an underhand debt acknowledgment that guarantees the title of title to land without being preceded by a principal agreement, as well as the judge's consideration (Ratio Decidendi) in the Cassation Decision Number 837K / Pdt / 2019 concerning default in the debt acknowledgment. The research method used in this study is a descriptive normative juridical approach, namely research that refers to the legal norms contained in statutory regulations and court decisions. The results of the research obtained by the author in this study are the first consideration of the judge in deciding Case Number 837 / K / Pdt / 2019 is not quite right because in theory the judge's decision overrides legal certainty for a civil case by deciding in default of a debt acknowledgment, which then the judge also also declared null and void the debt acknowledgment. Where based on the provisions of Article 12 of Law Number 4 of 1996 concerning Mortgage Rights, the guarantee which is the object of the author's research, is a forbidden cause that is contrary to the validity of an agreement, so that the legal consequences are null and void from the start without having to obey prior default in the debt recognition deed. So that the author's suggestion is necessary for parties who want to carry out lending and borrowing activities, especially in terms of debt and credit, first understand any rules and legal norms that apply to their actions, so that they will not cause losses among the parties who bind themselves in the future.